NutritionDay ICU: A 7 year worldwide prevalence study of nutrition practice in intensive care. Issue 4 (August 2017) - Bendavid, Itai; Singer, Pierre; Theilla, Miriam; Themessl-Huber, Michael; Sulz, Isabella; Mouhieddine, Mohamed; Schuh, Christian; Mora, Bruno; Hiesmayr, Michael
Summary: Introduction: To determine the nutrition practice in intensive care units and the associated outcome across the world, a yearly 1 day cross sectional audit was performed from 2007 to 2013. The data of this initiative called "nutritionDay ICU" were analyzed. Material and methods: A questionnaire translated in 17 languages was used to determine the unit's characteristics, patient's condition, nutrition condition and therapy as well as outcome. All the patients present in the morning of the 1 day prevalence study were included from 2007 to 2013. Results: 9777 patients from 46 countries and 880 units were included. Their SAPS 2 was median 38 (IQR 27–51), predicted mortality was 30.7% ± 26.9, and their SOFA score 4.5 ± 3.4 with median 4 (IQR 2–7). Administration of calories did not appear to be related to actual or ideal body weight within all BMI groups. Patients with a BMI <18.5 or >40 received slightly less calories than all other BMI groups. Two third of the patients were either ventilated or were in the ICU for longer than 24 h at nutritionDay. Routes of feeding used were the oral, enteral and parenteral routes. More than 40% of the patients were not fed during the first day. The mean energy administered using enteral route was 1286 ± 663 kcal/day and using parenteral nutrition 1440 ± 652 kcal/day. 60 days mortality was 26.0%. Discussion: This very large collaborative cohort study shows that most of the patients are underfed during according to actual recommendations their ICU stay. Prescribed calories appear to be ordered regardless to the ideal weight of the patient. Nutritional support is slow to start and never reaches the recommended targets. Parenteral nutrition prescription is increasing during the ICU stay but reaching only 20% of the population studied if ICU stay is one week or longer. The nutritional support worldwide does not seem to be guided by weight or disease but more to be standardized and limited to a certain level of calories. These observations are showing the poor observance to guidelines.